Wild house mice have a more dynamic and aerotolerant gut microbiota than laboratory mice - Hanski, Eveliina; Joseph, Susan; Curtis, Michael A.; Swann, James W.; Vallier, Marie; Linnenbrink, Miriam; Baines, John F.; Jensen, Jens-Kjeld; Wolfenden, Andrew; Mair, Iris; Else, Kathryn J.; Bradley, Janette E.; et al. (Springer Science and Business Media LLC, 2025)
The mammalian gut microbiota is a complex microbial community with diverse impacts on host biology. House mice (Mus musculus) are the major model organism for research on mammals, but laboratory domestication has altered their gut microbiota from that of their wild counterparts. Knowledge about how and why the gut microbiota of this species varies between lab and wild settings and among natural populations could improve its utility as a model organism. Here, we use a large dataset comprising over 800 house mouse samples from multiple laboratory facilities and strains and wild mice from mainland and island populations to investigate gut microbiota variation in this species across contrasting genetic and environmental settings. Across geographically disparate populations, we find that wild mice possess a gut microbiota that is compositionally distinct, displays a higher relative abundance and richness of aerotolerant taxa, and is taxonomically and functionally more diverse than that of lab mice. Longitudinally sampled wild mice also display markedly higher temporal turnover in microbiota composition than lab mice. Wild mice from oceanic islands harboured microbiotas that differed subtly from those of mainland wild mice and were more divergent from lab mouse microbiotas. These findings highlight much greater spatial and temporal turnover of gut microbes in wild compared to laboratory mice.